Benzanthric Acid, a Novel Metabolite From Streptomyces albus Del14 Expressing the Nybomycin Gene Cluster - Rodríguez Estévez, Marta; Gummerlich, Nils; Myronovskyi, Maksym; Zapp, Josef; Luzhetskyy, Andriy (Frontiers in Chemistry, 2020)
Streptomycetes constitute a diverse bacterial group able to produce a wide variety of secondary metabolites with potential applications in the pharmacy industry. However, the genes responsible for the biosynthesis of these compounds are very frequently inactive or expressed at very low levels under standard laboratory cultivation conditions. Therefore, the activation or upregulation of secondary metabolite biosynthesis genes is a crucial step for the discovery of new bioactive natural products. We have recently reported the discovery of the biosynthetic genes for the antibiotic nybomycin (nyb genes) in Streptomyces albus subsp. chlorinus. The nyb genes were expressed in the heterologous host Streptomyces albus Del14, which produces not only nybomycin, but also a novel compound. In this study, we describe the isolation, purification, and structure elucidation of the new substance named benzanthric acid.